1953
DOI: 10.1071/ar9530430
|View full text |Cite
|
Sign up to set email alerts
|

Studies in fleece-rot of sheep.

Abstract: Occasions of unduly heavy and prolonged rainfall during the period April 1946 – July 1951 resulted in the occurrence of fleece-rot in sheep of the Field Station flock in each of the six years. Data obtained from periodic examinations of the flock have been related to the nature of climatic conditions associated with outbreaks of the disease. They show that when rain occurs in falls of sufficient intensity and frequency to wet sheep to the skin for a period of a week or more, fleece-rot may be expected to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

1959
1959
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 3 publications
2
32
0
1
Order By: Relevance
“…The names dry yolk, cakey yolk, hard yolk also refer to this condition as seen in the non-active nhase after drying-out of the fleece. Hayman (1953Hayman ( , 1955 has agreed with Belschner and Seddon's earlier contention that this condition is brought abou~ by the action of bacteria on a serous exudate of the skin. This author also found that a predisposing factor in the formation of the exudate was a plentiful sunply of moisture.…”
Section: (H) Fleece Rotsupporting
confidence: 79%
See 1 more Smart Citation
“…The names dry yolk, cakey yolk, hard yolk also refer to this condition as seen in the non-active nhase after drying-out of the fleece. Hayman (1953Hayman ( , 1955 has agreed with Belschner and Seddon's earlier contention that this condition is brought abou~ by the action of bacteria on a serous exudate of the skin. This author also found that a predisposing factor in the formation of the exudate was a plentiful sunply of moisture.…”
Section: (H) Fleece Rotsupporting
confidence: 79%
“…to skin level and have little or no effect on the growth of micro-organisms and, even after heavy rain, the rapid drying out of the fleece (Fraser, 1957) limits the time available for active microbial growth and multiplication. The work of Hayman (1953) and Henderson (1955) has shown that sheep can be divided into two groups, those which are susceptible to bacterial discoloration of the wool and the growth of micro-organisms at the base of the fleece generally, and those which are resistant. Although the resistant and susceptible types of wool may be easily separated by subjective appraisal by an experienced wool man, the chemical orphysical bases for this separation are not known.…”
Section: Discussionmentioning
confidence: 99%
“…In many districts in New South Wales, Australia, (NSW) the average prevalence of fleece rot in yearlings is ∼ 25% pa and is greater in yearlings than adult sheep. Many of the organisms involved in fleece rot produce a pigment, typically bright green but also blue, orange, brown or pink (Hayman, 1953;Fraser and Mulcock, 1956). Some of this discolouration is nonscourable and results in price discounts due to colour.…”
Section: Fleece Rot and Foot Rotmentioning
confidence: 99%
“…It is characterized by superficial *The pH of the contents of a cyst containing disrupted wool measured at 8, 13, 24, and 36 weeks ranged from 6·8 to 8·0. dermatitis and a serous exudate which on drying causes matting of the wool fibres (Hayman 1953). The affected wool becomes hard and stringy and in severe cases may be easily plucked from abnormal areas of skin.…”
Section: Effect Of the Organism On Woolmentioning
confidence: 99%
“…The causative organism was an aerobic, mesophilic, spore-forming rod, and was capable of breaking wool into individual cells in vitro. Hayman (1953), in producing fleece rot experimentally, mentions a pink coloration and rotting which developed after incubating moist wool for 3 weeks. No mention is made of a causative organism.…”
Section: Effect Of the Organism On Woolmentioning
confidence: 99%